2019
DOI: 10.1177/0894439318823703
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Completion Times: A Comparative Analysis of Smartphone and PC Web Surveys

Abstract: This article compares the factors affecting completion times (CTs) to web survey questions when they are answered using two different devices: personal computers (PCs) and smartphones. Several studies have reported longer CTs when respondents use smartphones than PCs. This is a concern to survey researchers because longer CTs may increase respondent burden and the risk of breakoff. However, few studies have analyzed the specific reasons for the time difference. In this analysis, we analyzed timing data from 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Nearly all previous studies comparing response times across desktop and mobile device modes have found that web surveys take longer to complete on mobile devices than on desktop devices (Andreadis 2015;Antoun and Cernat 2019;Couper and Peterson 2017;Schlosser and Mays 2018). Moreover, meta analyses of 21 studies (Gummer and Roßmann 2015) and 26 studies (Couper and Peterson 2017) corroborate these results.…”
Section: Response Time As An Indicator For Survey Burden Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…Nearly all previous studies comparing response times across desktop and mobile device modes have found that web surveys take longer to complete on mobile devices than on desktop devices (Andreadis 2015;Antoun and Cernat 2019;Couper and Peterson 2017;Schlosser and Mays 2018). Moreover, meta analyses of 21 studies (Gummer and Roßmann 2015) and 26 studies (Couper and Peterson 2017) corroborate these results.…”
Section: Response Time As An Indicator For Survey Burden Analysismentioning
confidence: 97%
“…For these purposes, paradata offer objective indicators of response behaviour, data quality, and usability of the survey (e.g. Antoun and Cernat 2019;Brockhaus et al 2017;Couper and Peterson 2017;Mayerl and Giehl 2018;McClain et al 2019;Roßmann and Gummer 2016;Sendelbah et al 2016). Moreover, paradata can be used to reflect and interpret responses from a content perspective (Yan and Olson 2013) or to classify respondents' personalities based on indicators of response behaviour (Stieger and Reips 2010).…”
Section: The Rising Importance Of Paradata For Survey Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be aggravated in the case of long surveys as the respondent burden increases. Antoun & Cernat (2020), using LISS data, found that smartphone respondents took on average 40% longer than respondents using personal computers (PCs) to complete the survey, noting also that more respondents engaged in multitasking when using smartphones.…”
Section: Determinants Of Breakoffmentioning
confidence: 99%
“…The planned missing design is used to manipulate respondent burden as the shortened questionnaire modules are hypothesized to relieve respondent burden relative to the fulllength questionnaire module. Following previous theory and research, respondent burden is operationalized as survey duration, and reflected in breakoff rates and, accordingly, completion rates (Antoun and Cernat 2020;Bradburn 1978;Mavletova and Couper 2015;Peytchev 2009;Sharp and Frankel 1983;Steinbrecher et al 2015). Breakoff rates are computed as the percentage of eligible respondents who started the survey but did not complete it.…”
Section: Planned Missing Experiments and Respondent Burdenmentioning
confidence: 99%